Glyptotendipes Kieffer and Demeijerea Kruseman from Lake Winnipeg, Manitoba, Canada, with the description of four new species (Diptera: Chironomidae) - Sæther, Ole A. (Zootaxa, 2011)
Glyptotendipes Kieffer and Demeijerea Kruseman from Lake Winnipeg, Manitoba, Canada, are recorded, described or redescribed. Demeijerea spinulata sp. n., Glyptotendipes (G.) paratestaceus sp. n., G. (G.) paulisensus sp. n., and G. (G.) sensilis sp. n. are described as male imagines and G. (G.) paulisensus also as female imago. Partial redescriptions are given of: Demeijerea brachialis (Coquillett), Glyptotendipes (G.) barbipes (Staeger), G. (G.) paripes (Edwards), G. (G.) lobiferus (Say), and G. (Caulochironomus) dreisbachi Townes. A male probably belonging to G. (Caulochironomus) scirpi (Kieffer) is described. Keys are given to Nearctic males of Glyptotendipes subgen. Glyptotendipes and to known females of the subgenus.